103 Testicular Microlithiasis Defines a Subgroup of Azoospermic Men with Low Rates of Sperm Retrieval. Issue 1 (1st April 2022) - Dekalo, S; Barda, S; Pignanelli, M; Campbell, J
ABSTRACT: Introduction: Testicular microlithiasis is prevalent in sub-fertile men but data regarding its association with sperm retrieval rates in azoospermic men are lacking. Objective: To investigate the prevalence of testicular microlithiasis and its relationship with sperm retrieval rates and histopathology in azoospermic men. Methods: Eighty-six consecutive men underwent scrotal ultrasonography prior to microsurgical testicular sperm extraction (microTESE). Sperm retrieval rate, testicular histopathology, testicular size, reproductive hormone estimation, karyotyping, Y chromosome microdeletion analyses and the presence of varicocele and hydrocele were compared between men with and without testicular microlithiasis. Results: In total, sperm retrieval rate was 40%. Testicular microlithiasis was detected in 12 men (14%). In this subgroup, sperm retrieval rate was only 8% (1/12) as opposed to 45% (33/74) in azoospermic men with no evidence of microlithiasis (p=0.02). Mean right and left testicular diameters were significantly lower in the microlithiasis group compared to men without microlithiasis (2.4 cm vs. 3.2 cm and 2.4 cm vs. 3.3 cm, respectively, p=0.04). There was no significant difference in any other parameter between the groups (age, FSH levels, prevalence of XXY karyotype, Y chromosome microdeletions, sonographic varicoceles or hydroceles). All eleven patients with microlithiasis and no spermatozoa found were diagnosed with Sertoli cells only on histopathology. The patient with testicular microlithiasis and successful sperm extraction was diagnosed with mixed atrophy. Conclusions: Among our cohort of azoospermic men who underwent scrotal ultrasound prior to microTESE, the presence of testicular microlithiasis was associated with very low sperm retrieval rates. Larger, prospective studies should be conducted to strengthen our results. Disclosure: No